2009
DOI: 10.1213/ane.0b013e31818a6f32
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Perioperative Hyperglycemia in Children with Traumatic Brain Injury

Abstract: Background Hyperglycemia after traumatic brain injury (TBI) is associated with poor outcome. This study examined the incidence and risk factors for perioperative hyperglycemia in children with TBI. Methods A retrospective cohort study of children ≤ 13 years who underwent urgent or emergent craniotomy for TBI at Harborview Medical Center (level I Adult and Pediatric Trauma Center) between 1994 and 2004 was performed. Preoperative (Emergency department to general anesthesia start), intraoperative (during gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 31 publications
2
28
0
1
Order By: Relevance
“…25,26 In addition, surgical intervention leads to fluid shifts and blood loss. Secondary insults during craniotomy for TBI have been reported, 9,10,2732 and as evidenced by our data here, secondary insults are also common during orthopedic surgery in patients with TBI and may contribute to worse outcomes. Therefore, anesthesiologists can potentially contribute to improving TBI outcomes by reducing the burden of secondary insults during craniotomy as well as extracranial surgery.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…25,26 In addition, surgical intervention leads to fluid shifts and blood loss. Secondary insults during craniotomy for TBI have been reported, 9,10,2732 and as evidenced by our data here, secondary insults are also common during orthopedic surgery in patients with TBI and may contribute to worse outcomes. Therefore, anesthesiologists can potentially contribute to improving TBI outcomes by reducing the burden of secondary insults during craniotomy as well as extracranial surgery.…”
Section: Discussionsupporting
confidence: 78%
“…38 Although previous studies have examined secondary insults in the pre-hospital period, during transportation to a tertiary care center, in the emergency department and in the intensive care setting, 38 data on intraoperative secondary insults are limited. 9,10 Moreover, patients with TBI frequently have associated orthopedic injuries requiring surgical intervention and data on secondary insults during orthopedic surgery in TBI and their impact on neurological outcomes are sparse and old. 1114 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that approximately 10% of patients had at least 1 blood glucose reading of 150 mg/dl or higher dur- 17 studied a retrospective cohort of children under 13 years of age who presented with a head trauma and underwent emergency neurosurgery. They found blood glucose levels of 200 mg/ dl or higher in 32% of the patients during the intraoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…10Y14 One study found that 82% of neurosurgical pediatric patients with TBI had hyperglycemia preoperatively. 10 We have observed that infants admitted to our pediatric intensive care unit (PICU) with TBI often have hyperglycemic on initial presentation. We hypothesized that elevated serum glucose could be a sensitive marker for the presence of intracranial injury in infants who presented to the ED with a variety of symptoms.…”
mentioning
confidence: 99%